2018
DOI: 10.1016/j.physbeh.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Natural predator and a human stimulus differently affect the behavior, cortisol and cerebral hemisphere activity of marmoset monkeys

Abstract: The behavior, cortisol concentration and cerebral hemisphere activity of twelve marmoset monkeys were determined during standardized predatory stress-related events. Each subject was submitted to three 5-min trials, randomly held at 2-week intervals: a human intruder, a taxidermized oncilla cat and a no-stimulus control trial. Stimuli were positioned outside the home-cage and the ensuing reaction recorded. Baseline tympanic membrane temperature (TMT) was subtracted from the post-trial measure to determine chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…As noted above, Gordon and Rogers () measured reactivity of the monkeys in face of a novel task, while Braccini and Caine () measured responses to a fearful situation. Additional evidence that fearful situations induce right hemisphere activation in marmosets comes from a recent study using tympanic membrane temperature thermometry (Pereira, Duarte, Maior, & Barros, ). The authors found that changes in temperature after exposure to two types of threatening stimuli (human intruder or predator) were specific to the right ear (i.e, right hemisphere) in marmosets.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, Gordon and Rogers () measured reactivity of the monkeys in face of a novel task, while Braccini and Caine () measured responses to a fearful situation. Additional evidence that fearful situations induce right hemisphere activation in marmosets comes from a recent study using tympanic membrane temperature thermometry (Pereira, Duarte, Maior, & Barros, ). The authors found that changes in temperature after exposure to two types of threatening stimuli (human intruder or predator) were specific to the right ear (i.e, right hemisphere) in marmosets.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TMT increased bilaterally after a brief restraint event ( bushbabies : Hanbury et al, 2011 ), whereas a right-side dominance was seen after longer intervals ( marmosets : Pereira et al, 2019 ) or recurring episodes ( marmosets : Tomaz et al, 2003 ). On the other hand, brief exposures to a predator model were asymmetrically processed by the right hemisphere ( marmosets : Hook-Costigan and Rogers, 1998 ; Souza Silva et al, 2007 ; Pereira et al, 2018 ), but the response to a food-retrieval task associated with a predatory stimulus was blunted by unilateral lesions on either side ( macaques : Izquierdo and Murray, 2004 ). When processing emotionally-laden stimuli, aspects other than event duration may contribute to the variability in functional hemisphere bias, or even lack thereof, including the type of stimulus (e.g., restraint vs. predatory stress), species (e.g., response to unfamiliar human by marmosets vs. macaques; Izquierdo and Murray, 2004 ; Pereira et al, 2018 ) and trait-like characteristics (e.g., fearful temperament; Kalin et al, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…A dilution of 1:50 serum:diluent was used (Multi-diluent 3, Siemens, Brazil). CLIA and dilution parameters were based on a previous study in this species (Pereira et al, 2018 ). Assay sensitivity was 1 μg/dl, and inter- and intra-assay coefficient of variation from pooled serum were 9.8% and 7.5%, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations